Computed Tomographic Anatomy of Pancreas in Rajapalayam and Chippiparai Breeds of Dogs - Senthilkumar, S.; Kannan, T.A.; Velavan, A.; Kumary, S.Usha; Ramani, C.; Ramesh, Geetha (Indian Journal of Veterinary Anatomy, 2023)
Computed tomographic observations of pancreas in adult Rajapalayam and Chippiparai dog breeds was carried out in Madras Veterinary College and Teaching Hospital. The features evaluated include location, size, topographical correlations, boundaries and enhancement pattern and Hounsfield units (HU). Pancreas of Rajapalayam and Chippiparai breeds was located between twelth thoracic vertebra to first lumbar vertebra. In both the breeds pancreas consisted of body, right and left lobes in right side of abdominal cavity. Normal pancreas in CT imaging was thin, triangular in cross section and hypoattenuating to the spleen and showed uniformly contrast enhancement. The body of the pancreas was located adjacent to the cranial part of the duodenum. The right lobe of the pancreas was easily identified than the left lobe. Hounsfield units in pre and post contrast computed tomographic images were ranged between 52 - 70 HU.